Multi-scale complexity analysis of muscle coactivation during gait in children with cerebral palsy - Tao, Wen; Zhang, Xu; Chen, Xiang; Wu, De; Zhou, Ping (Frontiers in Human Neuroscience, 2015)
The objective of this study is to characterize complexity of lower-extremity muscle coactivation and coordination during gait in children with cerebral palsy (CP), children with typical development (TD) and healthy adults, by applying recently developed multivariate multi-scale entropy (MMSE) analysis to surface EMG signals. Eleven CP children (CP group), eight TD children and seven healthy adults (consider as an entire control group) were asked to walk while surface EMG signals were collected from 5 thigh muscles and 3 lower leg muscles on each leg (16 EMG channels in total). The 16-channel surface EMG data, recorded during a series of consecutive gait cycles, were simultaneously processed by multivariate empirical mode decomposition (MEMD), to generate fully aligned data scales for subsequent MMSE analysis. In order to conduct extensive examination of muscle coactivation complexity using the MEMD-enhanced MMSE, 14 data analysis schemes were designed by varying partial muscle combinations and time durations of data segments. Both TD children and healthy adults showed almost consistent MMSE curves over multiple scales for all the 14 schemes, without any significant difference (p > 0.09). However, quite diversity in MMSE curve was observed in the CP group when compared with those in the control group. There appears to be diverse neuropathological processes in CP that may affect dynamical complexity of muscle coactivation and coordination during gait. The abnormal complexity patterns emerging in CP group can be attributed to different factors such as motor control impairments, loss of muscle couplings, and spasticity or paralysis in individual muscles. All these findings expand our knowledge of neuropathology of CP from a novel point of view of muscle co-activation complexity, also indicating the potential to derive a quantitative index for assessing muscle activation characteristics as well as motor function in CP.